Bactericidal Effect of Pseudomonas oryziphila sp. nov., a Novel Pseudomonas Species Against Xanthomonas oryzae Reduces Disease Severity of Bacterial Leaf Streak of Rice - Yang, Ruihuan; Li, Shengzhang; Li, Yilang; Yan, Yichao; Fang, Yuan; Zou, Lifang; Chen, Gongyou (Frontiers in Microbiology, 2021)
Pseudomonas is a diverse genus of Gammaproteobacteria with increasing novel species exhibiting versatile trains including antimicrobial and insecticidal activity, as well as plant growth-promoting, which make them well suited as biocontrol agents of some pathogens. Here we isolated a strain 1257 that exhibited strong antagonistic activity against two pathovars of Xanthomonas oryzae, especially X. oryzae pv. oryzicola (Xoc) responsible for the bacterial leaf streak (BLS) in rice. The phylogenetic, genomic, physiological and biochemical characteristics support that strain 1257 is a representative of a novel Pseudomonas species that is most closely related to the entomopathogenic bacterium P. entomophila. We propose to name it Pseudomonas oryziphila sp. nov. Comparative genomics analyses showed that P. oryziphila 1257 possesses most of the central metabolic genes of two closely related strains P. entomophila L48 and P. mosselii CFML 90-83, as well as a set of genes encoding the type IV pilus system, suggesting that it versatile metabolism and motility properties. Some features such as insecticidal toxins, phosphate solubilization, indole-3-acetic acid (IAA) and phenylacetic acid (PAA) degradation were disclosed. Genome-wide random mutagenesis revealed that the non-ribosomal peptide catalyzed by LgrD may be a major active compound of P. oryziphila 1257 against Xoc RS105, as well as the critical role of the carbamoyl phosphate (CP) and the pentose phosphate pathway (PPP) that control the biosynthesis of this target compound. Our findings demonstrate that 1257 could effectively inhibit the growth and migration of Xoc in rice tissue to prevent the BLS disease. To our knowledge this is the first report of a novel Pseudomonas species that displays a strong antibacterial activity against Xoc. The results suggest that the P. oryziphila strain could be a promising biological control agent for BLS.